2003
DOI: 10.1042/bj20021308
|View full text |Cite
|
Sign up to set email alerts
|

Regulation of tensin-promoted cell migration by its focal adhesion binding and Src homology domain 2

Abstract: Tensin1 is an actin- and phosphotyrosine-binding protein that localizes to focal adhesions. Recently, we have shown that both tensin1 and a new family member, tensin2, promote cell migration [Chen, Duncan, Bozorgchami and Lo (2002) Proc. Natl. Acad. Sci. U.S.A. 99, 733-738]. Since localization of proteins to particular intracellular compartments often regulates their functions, and Src homology domain 2 may mediate signals related to cell migration, we hypothesize that tensin-mediated cell migration is regulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
49
1

Year Published

2004
2004
2015
2015

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(53 citation statements)
references
References 34 publications
3
49
1
Order By: Relevance
“…Our data therefore strongly suggest that tensin binding has a RhoGAPindependent role that contributes to the biological activity of DLC. Our biochemical analyses provide a potential alternate mechanism because we observe that DLC1 can compete with ␤3-integrin for binding the PTB domain and with several proteins for binding the SH2 domain; a previous mutant analysis of tensin1 reported that both of these tensin domains are required for tensin-dependent migration (24). Thus, DLC1, and presumably the other DLC family members, is a multifunctional protein whose tensin binding and RhoGAP activities do not depend on each other, but both activities are required for biological activity.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Our data therefore strongly suggest that tensin binding has a RhoGAPindependent role that contributes to the biological activity of DLC. Our biochemical analyses provide a potential alternate mechanism because we observe that DLC1 can compete with ␤3-integrin for binding the PTB domain and with several proteins for binding the SH2 domain; a previous mutant analysis of tensin1 reported that both of these tensin domains are required for tensin-dependent migration (24). Thus, DLC1, and presumably the other DLC family members, is a multifunctional protein whose tensin binding and RhoGAP activities do not depend on each other, but both activities are required for biological activity.…”
Section: Discussionmentioning
confidence: 99%
“…The tensin PTB domain binds the intracellular portion of several ␤-integrins, including ␤3-integrin (26), and is required for tensin-dependent cell migration (24). Given that DLC1 binds the tensin PTB domain, we speculated that DLC1 might compete with ␤3-integrin for binding and that similar sequences in the PTB domain might be required for binding each protein.…”
Section: Dlc1 Competes With ␤3-integrin For Binding To the Tensin Ptbmentioning
confidence: 99%
“…3) Low levels of FGFR1 are expressed, and the cells are efficiently stimulated by bFGF (37); thus, the specific effects of VHL knock-down on FGFR signaling can be observed unambiguously. 4) HEK293 cells possess a moderate capacity of chemotactic migration toward serum (38). Also, we expressed either wild type HIF-2␣ (HIF-2␣ (WT)) or a constitutively active HIF-2␣ (HIF-2␣ (P/A)) in order to delineate HIF-dependent and -independent roles of VHL.…”
Section: Fgfr1 and Erk Activities Regulate Cell Migration In Vhl Mutantmentioning
confidence: 99%
“…Tensin is particularly interesting in the myriad of focal adhesion proteins because it can bind to actin microfilaments at multiple sites (Lo et al 1994b), enabling tensin both to cap the growing ends of actin filaments and to crosslink actin filaments (Lo et al 1994b;Chuang et al 1995). In addition, tensin is phosphorylated on tyrosine residues (Salgia et al 1995) and contains an SH2 domain (Davis et al 1991), suggesting that tensin might participate in signal transduction cascades relevant to various cellular functions, including cell migration (Chen et al 2002;Chen and Lo 2003), differentiation (Hiura et al 1995), regeneration (Ishii and Lo 2001), and apoptosis (Kook et al 2003). Several factors, including the ECM, platelet-derived growth factor, thrombin, angiotensin, and oncogenes, induce tensin-mediated signal transduction (Chen et al 2002).…”
Section: Discussionmentioning
confidence: 99%